P102 Quantitative biological imaging of plasmid DNA in live human airway epithelial cells following non-viral gene transfer. (16th November 2010) - Singh, C; Munkonge, F M; Smith, S N; Griesenbach, U; Carzaniga, R; Tillmann, P; Cheng, S; Rogers, A; Dewar, A; Alton, E W F W
Abstract : We are interested in non-viral gene therapy for cystic fibrosis (CF). It is widely accepted that in addition to extracellular barriers responsible for inefficient uptake, there are key intracellular obstacles to the nuclear delivery of the therapeutic plasmid DNA (pDNA). Thus, we are investigating the intracellular fate of pDNA following transfection, using the clinically relevant cationic Genzyme Lipid (GL) 67 formulation, using three-dimensional Spinning-Disk real-time confocal, combined with transmission electron microscopy (TEM) to track, quantitate and provide high resolution 'snapshots' of pDNA at the single molecule level in transfected primaryhuman airway epithelial cells (AECs) grown at the air–liquid interface (hALI). The pDNA was tagged with fluorescent, photostable semiconductor quantum dots (Qdot-pDNA) or 1.4 nm gold nanoparticles (Au-pDNA) for use in fluorescence or TEM studies, respectively. Both confocal microscopy and TEM experiments demonstrate that Lipid GL67 was able to transfect AECs with Qdot- and Au-pDNA. The number of gold spots in the nuclei of Au-pDNA-transfected AECs compared with those in unconjugated-pDNA-transfected control cells was significantly higher (p<0.05, n=5 independent experiments). Approximately 50% of the total internalised pDNA localised to nuclei within 1 h post-transfection in both confocal (123 AECs, eight independent experiments) and TEM (40 AECs, five independent experiments) studies. Thus, within 1 h pDNA is equally distributed between the cytoplasm and the nucleus in well differentiated human ALIs following non-viral-based gene transfer. Experiments are now underway to track the intracellular trafficking of the pDNA at earlier time points.